Effect of caffeine consumption on the risk for neurological and psychiatric disorders: Sex differences in human - Jee, Hye Jin; Lee, Sang Goo; Bormate, Katrina Joy; Jung, Yi Sook (Nutrients, 2020)
Caffeine occurs naturally in various foods, such as coffee, tea, and cocoa, and it has been used safely as a mild stimulant for a long time. However, excessive caffeine consumption (1~1.5 g/day) can cause caffeine poisoning (caffeinism), which includes symptoms such as anxiety, agitation, insomnia, and gastrointestinal disorders. Recently, there has been increasing interest in the effect of caffeine consumption as a protective factor or risk factor for neurological and psychiatric disorders. Currently, the importance of personalized medicine is being emphasized, and research on sex/gender differences needs to be conducted. Our review focuses on the effect of caffeine consumption on several neurological and psychiatric disorders with respect to sex differences to provide a better understanding of caffeine use as a risk or protective factor for those disorders. The findings may help establish new strategies for developing sex‐specific caffeine therapies.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Caffeine; Dose-Response Relationship, Drug; Female; Humans; Male; Mental Disorders; Middle Aged; Nervous System Diseases; Risk Assessment; Risk Factors; Sex Characteristics; Young Adult; Caffeine; Dementia; Depression; Neurological and psychiatric disorders; Sex differences; Sleep disorder; Stroke